Comparative Effects of Maturity and Processing on Chemical Composition and Bioactivities in Toona sinensis Leaves - Guohuo Wu; Zhaoyun Chen; Yan Tang; Shuolei Xu; Wenli Fan; Li Wu; Yuntao Ji; Changqing Qu (Foods)
Toona sinensis (“Heiyouchun”) is a traditional Chinese woody vegetable, the leaves of which can also be processed into tea, known for its distinctive flavor and diverse bioactivities. However, the effects of leaf maturity and processing methods on its phytochemical composition and functional properties remain unclear. In this study, metabolomic analysis revealed 35 significantly different metabolites between tender and mature leaves, with higher concentrations of flavonoids, flavonoid glycosides, limonoids, and amino acids in tender leaves. Additionally, comparative analysis revealed that black tea fermentation preserves bioactive compounds more effectively than hot-air drying, particularly in tender leaves. In vitro activity assays showed that toon leaf tea extracts exhibited significant antioxidant and hypoglycemic effects, with black tea fermented tender leaves displaying the most potent bioactivity. Correlation analysis further confirmed a strong positive relationship between flavonoid/polyphenol content and bioactivity. These findings provide a theoretical foundation for optimizing processing techniques to enhance the functional properties of toon leaf tea.